Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1074/jbc.m409977200
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Promoters and Developmentally Regulated 5′- and 3′-mRNA Untranslated Regions of the Mouse Scn5a Cardiac Sodium Channel

Abstract: The SCN5A gene encodes a voltage-sensitive sodium channel expressed in cardiac and skeletal muscle. Coding region mutations cause cardiac sudden death syndromes and conduction system failure. Polymorphisms in the 5-sequence adjacent to the SCN5A gene have been linked to cardiac arrhythmias. We identified three alternative 5-splice variants (1A, 1B, and 1C) of the untranslated exon 1 and two 3-variants in the murine Scn5a mRNA. Two of the exon 1 isoforms (1B and 1C) were novel when compared with the published h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…To reveal the functional role of Nav1.7 channel expression in IDC, we demonstrated that expression of the Nav1.7 channel in (38,39). Furthermore, they are also implicated as key regulators of intracellular pH and cell migration (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…To reveal the functional role of Nav1.7 channel expression in IDC, we demonstrated that expression of the Nav1.7 channel in (38,39). Furthermore, they are also implicated as key regulators of intracellular pH and cell migration (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that the cardiac sodium channel (SCN5a) promoter region contains an NF-B response element that could lead to Na ϩ channel transcriptional regulation by an NF-B-dependent mechanism (16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have defined the scn5a promoter region (36). For these experiments, a new promoter construct that contained the NF-B consensus binding site was used to test the effect of treatments on scn5a transcription.…”
Section: Methodsmentioning
confidence: 99%
“…NF-B is a known redox-sensitive transcription factor (50). Previously, we have shown that the promoter region of the cardiac Na ϩ channel contains one NF-B consensus binding sequence (36). Therefore, we investigated whether NF-B might be involved in the ANG II-or H 2 O 2 -mediated Na ϩ channel transcriptional regulation.…”
Section: ;mentioning
confidence: 99%
See 1 more Smart Citation